Terapia por diodo emissor de luz 630 nm reduz hiperalgesia mecânica inflamatória por meio da ativação de receptores endotelinérgicos / opioidérgicos: análise da influência da potência em camundongos machos e fêmeas - Oliveira, Bruna Hoffmann (2019)
Introduction: In LEDT studies, apart from wavelength (in nanometers - nm), energy density or dose (in Joules(J)/cm2) is a key factor; although depending on irradiance [in milliwatts(mW)/cm2 - which in turn depends on the device’s radiant power (in mW)], very different irradiation times are necessary to yield the same energy density or dose. In spite of its importance, there are no studies that investigate the biological effects and endogenous mechanisms elicited by different LEDT irradiances (given a constant treatment dose and wavelength). Objectives: This study evaluated the effect of two different LEDT irradiances (3.5 and 90 mW/cm2) – at a wavelength of 630 nm and dose of (2 J/cm2) – on mechanical hyperalgesia following CFA i.pl. injection in mice. Additionally, the role of peripheral opioid and endothelin-B receptors (ETB-R), as well as the influence of sex was investigated. Methods: Different groups of male or female mice were evaluated 6 and 96 hours after intraplantar (i.pl.) injection of Complete Freund's Adjuvant (CFA). Mechanical hyperalgesia was evaluated 30 min after treatments. Administration of naloxone (an opioid antagonist) or Bq-788 (an ETB-R antagonist) fifteen minutes before LEDT or Sarafotoxin S6c (SRTX S6c, ETB-R agonist) treatments, helped determine the involvement of peripheral opioid and ETB-Rs on LEDT. Lastly, paw skin immunocontent of ETB-Rs of both male and female mice was quantified after consecutive daily treatments with LEDT. Results: LEDT at an irradiance of 90mW/cm2, increased mechanical threshold in male and female mice, both 6 and 96h after CFA injection, although minor variations in response were observed between sexes. Bq-788 and naloxone administration prevented the effect of LEDT and SRTX S6c; however, LEDT did not influence the immunocontent of peripheral ETB-Rs. Conclusion: The results suggest that irradiance influences LEDT effect; and that activation of opioid and ETB receptors play an important role in LEDT induced analgesia. Although minor variations in response were observed between sexes, it does not appear that LEDT effects are sex-dependent.